IMPLEMENTASI MODEL BLENDED LEARNING DALAM PEMBELAJARAN PADA GURU-GURU SEKOLAH DASAR DI DESA WAIMITAL - Tamalene, Hanisa; Ratumanan, Tanwey Gerson (Universitas Pattimura, 2021)
This community service activity aims to (1) improve the understanding of teachers of SD Negeri 1 and SD Negeri 3 Waimital about learning models Blended Learning, (2) produce lesson plans by using the learning model Blended Learning. The achievement of these goals is carried out through the provision of materials and training with lecture methods, questions and answers, demonstrations, and exercises (tutorials), when the activity takes place, monitoring is carried out by resource persons to see and assist teachers in making based lesson plans Blended Learning. The results show that the service program is going well and smoothly. This program is able to improve the understanding ability of teachers about models and teachers are able to make lesson plans based Blended Learning. The target of this activity is elementary school teachers in Waimital Village